Associations de solidarité internationale. Répertoire 2000 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Associations de solidarité internationale. Répertoire 2000 Association Ibiscus 1 bis, rue du Havre 75008 Paris, France Fax : + 33 1 42 94 25 91 E-mail : ibis@ibiscus.fr Site Web : www.ibiscus.fr 219 pages ISBN 2-90994 -23-6 Prix : 80 FF •